Prevalência de deficiência de vitamina D e análise dos fatores associados em crianças saudáveis do ambulatório de pediatria do HUSM - Silva, Alliny Beletini da (2016)
Vitamin D deficiency is one of the most commented health issues at the moment, given the number of discoveries about its function in various tissues and organs. The principal action of vitamin D is related to calcium absorption and its implication in bone homeostasis, but, besides this, it has been implicated in several other diseases. Despite this huge interest in vitamin D, there are still few studies talking about vitamin D deficiency in children in our country, and especially in our region. Knowing the prevalence of vitamin D deficiency in specific place or region, it will be possible plan actions focusing prevention, early diagnosis and treatment, and thus to reduce complications and costs to public health. This study aims to determine the prevalence of vitamin D deficiency and the factors associated in healthy children of the outpatient pediatrics clinic of a university hospital in the central region of Rio Grande do Sul. This analytical cross-sectional study included 138 healthy children of the pediatrics clinic of the University Hospital of Santa Maria. The serum 25 (OH) D was performed by the Clinical Laboratory of the University Hospital. The associated factors were obtained through a questionnaire conducted by telephone. The results showed that the overall prevalence of vitamin D deficiency in the population studied was 42.7%, 12.3% with deficiency and 30.4% with insufficiency in vitamin D. The highest percentage of children with adequate levels occurred among infants, followed by preschoolers, schoolers and adolescents. The majority, 65.9%, received vitamin D supplementation on average by 21.6 (± 15.6) months. The principal risk factors identified were: the age group (preschoolers, schoolers and adolescents); residence in urban areas; no supplemental of vitamin D and lack of sun exposure. We conclude that the prevalence of vitamin D deficiency is high in the region studied, especially among adolescents. Besides age, no vitamin D supplementation and inadequate sunlight exposure are risk factors that increase the chance of insufficiency/deficiency in vitamin D.